Acute Psychiatric Hospitalization of the Mentally Ill in the Metropolis: An Empirical Study - George E. Dix (Washington University Law Quarterly, 1968)
Part I describes the development of the legal framework for legally-proscribed criteria for nonvoluntary hospitalization. Part II is a description of how the purportedly regulated system actually works, applied at various points in the process. While the discussion is structured as a description of the steps from the community to full-time hospitalization, the descriptions and the illustrative examples should present a fairly complete picture of the variety of situations with which a metropolitan public acute psychiatric hospitalization service is called upon to deal. Part III is a discussion of one central legal issue, the role of the judiciary in the hospitalization process, in light of the conclusions reached in Parts I and II.
Keywords: Mental health; Psychiatry